Kandungan Mineral Ã¢â‚¬Å“NikeÃ¢â‚¬Â Ikan Payangkah (Ophiocara aporos ) dari Danau Tondano di Sulawesi Utara - Sofia Krisen; Jeanne Tuerah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
Research has been conducted on the Mineral Content of Ã¢â‚¬Å“nikeÃ¢â‚¬Â Payangkah fish (O. aporos ) from Lake Tondano in North Sulawesi. The research objective was to determine the levels of Calcium, Magnesium, Manganese and Phosphorus.